GOOD TO GREAT EFFECT – CASE STUDY AT MERDEKA CHOPPER GOLD, TBK - M. Syafnur; Fauzi Fauzi; Aulia Dewi Gizta; M. Isa Alamsyahbana; Novi Chandra Saputra (PENANOMICS: International Journal of Economics, 2022)
Good to Great effect is a concept developed by one of the writers and researchers named Jim Colins, where according to him there are companies that have above good abilities which then lead the company to become a great company. In this study, the researcher took one of the companies that have these indications, although currently being hit by the Covid 19 pandemic, the company's performance continues to increase. The population of this study are companies in LQ45 with a sample that is engaged in mining. The data analysis method uses financial report indicators for 5 years running fundamental analysis and stock return analysis. The results show that the MDKA company meets the characteristics as a Good to Great Effect company.